(609) البرنامج التدريبى طويل الأجل لموظفى وزارة الادارة المحلية - عز الدين همام أحمد (معهد التخطيط القومى, 2026)
ملخص تتناول هذه المذكرة البحثية التي أعدها الدكتور عز الدين همام أحمد عام ١٩٦٥ مبادئ النظرية الاقتصادية الجزئية، حيث تبدأ بتحليل طبيعة الحاجات الإنسانية المتزايدة وندرة الموارد المتاحة لإشباعها، مما يفرض ضرورة المفاضلة والاختيار العلمي في توزيع الموارد. وتعرف المذكرة علم الاقتصاد بأنه البحث في تنظيم الموارد المحدودة ذات الاستعمالات المختلفة لتحقيق أكبر إنتاج ممكن، مستعرضة عناصر الإنتاج الأربعة وهي الطبيعة والعمل ورأس المال والتنظيم، مع شرح مفصل لمفهوم الإنتاج بوصفه خلقاً للمنفعة أو زيادة فيها، وتوضيح أثر التخصص وتقسيم العمل في رفع الكفاءة الإنتاجية، بالإضافة إلى تحليل "قانون تناقص الغلة" الذي يحكم العلاقة بين العناصر الثابتة والمتغيرة في العملية الإنتاجية. كما يتعمق الملف في شرح نظرية الأثمان وآليات عمل السوق في ظل المنافسة الحرة، مبيناً كيفية تحديد سعر التوازن من خلال التفاعل المستمر بين قوى العرض والطلب. وتفصل الدراسة المفاهيم المرتبطة بمرونة الطلب والعوامل المؤثرة فيها مثل وجود البدائل وطبيعة السلعة، فضلاً عن استعراض أشكال المشروعات القانونية من منشآت فردية وشركات مساهمة وتعاونيات، مؤكدة أن المنظم يلعب دوراً محورياً في تحقيق التوازن بين الإنتاج والاستهلاك من خلال قراراته الاستثمارية وتنبؤاته بأحوال السوق، مما يجعل هذه المذكرة مرجعاً تعليمياً شاملاً يربط بين الأسس النظرية للاقتصاد الجزئي والتطبيقات العملية لإدارة الموارد القومية. This research paper, prepared by Dr. Ezz El-Din Hammam Ahmed in 1965, addresses the principles of microeconomic theory. It begins by analyzing the nature of increasing human needs and the scarcity of resources available to satisfy them, which necessitates a scientific approach to resource allocation. The paper defines economics as the study of organizing limited resources with various uses to achieve the greatest possible output. It reviews the four factors of production: nature, labor, capital, and organization, providing a detailed explanation of the concept of production as the creation or increase of utility. It also clarifies the impact of specialization and the division of labor on increasing productive efficiency, in addition to analyzing the "law of diminishing returns," which governs the relationship between fixed and variable elements in the production process . The document also delves into the theory of prices and the mechanisms of the market under free competition, explaining how the equilibrium price is determined through the continuous interaction between supply and demand forces. The study details the concepts related to the elasticity of demand and the factors affecting it, such as the availability of substitutes and the nature of the good. It also reviews the forms of legal enterprises, from sole proprietorships and joint-stock companies to cooperatives, emphasizing that the regulator plays a pivotal role in achieving a balance between production and consumption through its investment decisions and market forecasts. This makes the document a comprehensive educational reference that links the theoretical foundations of microeconomics with the practical applications of national resource management .